Analysis of miRNAs responsive to long‐term calcium deficiency in tef (Eragrostis tef (Zucc.) Trotter). (10th May 2022) - Numan, Muhammad; Guo, Wanli; Choi, Sang‐Chul; Wang, Xuegeng; Du, Boxuan; Jin, Weibo; Bhandari, Ramji Kumar; Ligaba‐Osena, Ayalew
Abstract: MicroRNAs (miRNAs) play an important role in growth, development, stress resilience, and epigenetic modifications of plants. However, the effect of calcium (Ca 2+ ) deficiency on miRNA expression in the orphan crop tef ( Eragrostis tef) remains unknown. In this study, we analyzed expression of miRNAs in roots and shoots of tef in response to Ca 2+ treatment. miRNA‐seq followed by bioinformatic analysis allowed us to identify a large number of small RNAs (sRNAs) ranging from 17 to 35 nt in length. A total of 1380 miRNAs were identified in tef experiencing long‐term Ca 2+ deficiency while 1495 miRNAs were detected in control plants. Among the miRNAs identified in this study, 161 miRNAs were similar with those previously characterized in other plant species and 348 miRNAs were novel, while the remaining miRNAs were uncharacterized. Putative target genes and their functions were predicted for all the known and novel miRNAs that we identified. Based on gene ontology (GO) analysis, the predicted target genes are known to have various biological and molecular functions including calcium uptake and transport. Pairwise comparison of differentially expressed miRNAs revealed that some miRNAs were specifically enriched in roots or shoots of low Ca 2+ ‐treated plants. Further characterization of the miRNAs and their targets identified in this study may help in understanding Ca 2+ deficiency responses in tef and related orphan crops.